2020
DOI: 10.1134/s1560090420030045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chromone Functionalized Chitosan Polymer: Application/Screening of Its Physical Parameters

Abstract: Chitosan is naturally occurring, biodegradable, non-toxic, non-allergenic biopolysaccharide derived from chitin which turns viscous upon dissolution in mildly acidic medium. Artificially changed chitosan consolidating hydroxyl chromone was set up by responding 6-Hydroxy-4-oxo-4H-chromone-3-carbaldehyde with chitosan; it was found to have high specific and chelating proficiency towards transition metal ion at pH 1-8. Enhanced adsorption capacity and a strong affinity for Cu 2+ was observed as compared to Cd 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Gaidhane et al used chitosan, which is a naturally occurring, environment-friendly bio-polysaccharide derived from chitin to synthesize a new chromone-based polymer 26. 82 Yang et al reported a new probe i.e., 6-ethoxychromone-3 carbaldehyde-(furanyl)hydrazone 33 with turn-on uorescence and colorimetric properties. 83 The dual functional probe 33 was designed by reuxing a mixture of furan-2-carbohydrazide 32 and 6-ethoxychromon-3-carbaldehyde 31 in acetonitrile for 24 hours (Scheme 9).…”
Section: Copper Detection By Chromonebased Schiff Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaidhane et al used chitosan, which is a naturally occurring, environment-friendly bio-polysaccharide derived from chitin to synthesize a new chromone-based polymer 26. 82 Yang et al reported a new probe i.e., 6-ethoxychromone-3 carbaldehyde-(furanyl)hydrazone 33 with turn-on uorescence and colorimetric properties. 83 The dual functional probe 33 was designed by reuxing a mixture of furan-2-carbohydrazide 32 and 6-ethoxychromon-3-carbaldehyde 31 in acetonitrile for 24 hours (Scheme 9).…”
Section: Copper Detection By Chromonebased Schiff Basesmentioning
confidence: 99%
“…Gaidhane et al used chitosan, which is a naturally occurring, environment-friendly bio-polysaccharide derived from chitin to synthesize a new chromone-based polymer 26. 82 Polymer 26 was prepared by the treatment of 24 with chitosan 25 in deionized water ( Scheme 8 ). It displayed specific, selective, and pH-influenced chelating efficiency with Cu 2+ ions in comparison to Ni 2+ , Co 2+ , and Cd 2+ heavy metal ions.…”
Section: Copper Detection By Chromone-based Schiff Basesmentioning
confidence: 99%
“…PEG is the covalent link of nonpoisonous, hydrophilic polyethylene glycol (PEG) to dynamic pharmaceutical constituents [18]. The technology established from revolutionary work was conducted in the 1950s and 1960s on the coupling of polymers to protein.…”
mentioning
confidence: 99%